Mathematics teacher education in the public interest : equity and social justice - Jacobsen, Laura J.; Mistele, Jean; Sriraman, Bharath (Emerald Publishing Limited : Information Age Publishing, Inc., 2012)
Mathematics teacher education has a critical role to play in preparing teachers to put at center stage goals to support equity in mathematics education and to diversify student interest and participation in mathematics. These goals must also resonate with broader public interest goals to improve educational and social conditions both in the U.S. and abroad. The Mathematics Teacher Education in the Public Interest book aims to support mathematics teacher educators to prepare teachers with new knowledge and skills to support all students to learn mathematics and to become informed, engaged, and critical citizens within their community, nation, and world. While internationally there is considerable interest among mathematics educators in issues of equity and social justice, the literature on mathematics teacher education for equity and social justice thus far has been very limited.The book provides theoretical discussions on the need for equity and social justice emphases in mathematics teacher education, as well as practical examples from mathematics teacher educators, documenting their own professional efforts to center practices on equity and social justice. Section emphases include critical perspectives on mathematics teacher education, the use of equity and social justice-themed activities in mathematics teacher preparation courses, and issues of identity and community and cultural contexts in mathematics teacher education. In addition syntheses of major ideas of the book are offered by experienced researchers.
Keywords: Mathematics teachers -- Training of.; Mathematics -- Study and teaching -- Social aspects.; Educational equalization.; Mathematics -- Study & Teaching.; Education.; Mathematics.; Teaching of a specific subject.; elektronické knihy; electronic books